REACH Beyond Borders Europeanization Towards Global Regulation - Filipec, Ondřej; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book discusses how much other countries reflect the EU chemical regulation REACH (Registration, Evaluation, Authorization, Restriction of Chemicals), in the context of Europeanization theory. The main hypothesis verified in this book is that more trade with the EU means more Europeanization (as the non-EU companies exporting to the EU have an obligation to comply with EU rules according to the "No data, No Market" REACH provision).  This book further points out that non-EU companies voluntarily adopt EU standards while this change has yet to be reflected on the policy level in non-EU countries, mainly for economic reasons. Exploring changes in national chemical regulatory policies among top chemical producers around the World brings new ideas into the process of Europeanization behind EU borders and provides useful material for academia, regulatory experts and export oriented chemical industry.
Introduction -- 1 The Concept of Europeanization -- 2 REACH as the source of Europeanization -- 3 Global Sources of Influence -- 4 REACH going to the EU Neighborhood -- 5 Europeanization of US Chemical Policy -- 6 REACH and BRIC Countries -- 7 REACH and the Far East -- 8 Exotic Dimensions of REACH -- 9 REACH and 'The rest of the World' -- 10 The Implications of REACH -- Conclusions.
Keywords: Chemistry, Technical; Europe -- Economic integration; Environmental policy; Industrial organization; Environmental law, International; Industrial Chemistry; European Economic Integration; Environmental Policy; Industrial Organization; International Environmental Law